1995
DOI: 10.1111/j.1365-2141.1995.tb05253.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CBFB/MYH11 transcripts in patients with inversion and other abnormalities of chromosome 16 at presentation and remission

Abstract: The pericentric inversion of chromosome 16 [inv(16)(p13q22)] and t(16;16)(p13;q22) are chromosomal rearrangements frequently associated with AML FAB type M4Eo resulting in the production of a fusion gene CBFB/MYH11. We studied 17 patients with a chromosome 16 abnormality (eight M4Eo, two M1, one M2, three M4 without abnormal eosinophils, three MDS) for the presence of CBFB/MYH11 transcripts using an RT-PCR technique. 10 AML patients with inv(16) tested RT-PCR positive (eight at presentation, one in remission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 16 publications
2
49
0
2
Order By: Relevance
“…6 The sensitivity of the PCR test has allowed it to kaemia (AML). The levels of the leukaemia-specific transcripts be used to monitor residual disease following treatment, 4,6,7 are expressed as a ratio to a ubiquitously expressed mRNA species (Abl) which controls for RNA degradation. This techand PCR positivity has been found in patients in long-term nique has been applied to 75 consecutive patients presenting remission.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 The sensitivity of the PCR test has allowed it to kaemia (AML). The levels of the leukaemia-specific transcripts be used to monitor residual disease following treatment, 4,6,7 are expressed as a ratio to a ubiquitously expressed mRNA species (Abl) which controls for RNA degradation. This techand PCR positivity has been found in patients in long-term nique has been applied to 75 consecutive patients presenting remission.…”
mentioning
confidence: 99%
“…This techand PCR positivity has been found in patients in long-term nique has been applied to 75 consecutive patients presenting remission. 6,7 with either de novo AML or tMDS; 6/75 patients analysed wereIn a study of four patients with inversion (16) in patients in complete remission. …”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] Indeed, using highly sensitive two-step conventional RT-PCR assays, most authors found AML1/ETO transcripts in almost all patients in CR, even many years after the end of therapy, when they might reasonably be considered cured of their disease. [11][12][13] This latter finding called into question the role of the fusion gene as the unique mutational event involved in the leukemogenesis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…One group detected the persistence of CBFB-MYH11 in long-term remission after allogeneic BMT using nested PCR. 173 In contrast, others have reported the disappearance of CBFB-MYH11 transcripts in patients with long-term follow-up. [174][175][176][177][178] It will be important to determine the clinical value of CBFB-MYH11 monitoring in larger series.…”
Section: Figure 18mentioning
confidence: 99%